Doença de chagas canina: análise de fatores de risco e educação em saúde - Silva, Luanna Fernandes (Universidade Federal Rural do Semi-Árido, 2014)
Chagas disease affects humans and many animals susceptible, among which dogs are considered the main reservoir in the domestic cycle, and the diagnosis in this important species for assessing the risk of transmission to the population in a region. The successful control and prevention requires knowledge among the population about the disease and ways to avoid it. In this context, we observe the Community Health Agents (CHA), working in the dissemination of information on these and other endemic diseases. Thus, the present study aimed to evaluate the knowledge about Chagas disease by owners of dogs positive for the disease and, in addition, verify that the CHA active in the neighborhoods where these owners reside, know Chagas disease to perform a job education in satisfactory health, and to assess whether these agents include the prevention of disease in their daily work and municipal management empowers and provides working conditions for these professionals. Several interviews with 34 owners of dogs seropositive for Chagas disease and 48 were performed with CHA. In both cases was used a semi-structured questionnaire with open and closed questions about Chagas disease, and for CHA, were added questions about the prevention and control activities performed by them and about the conditions of work offered for these professionals. In addition, at the time of the visit to interview the owners, blood was collected from seropositive dogs to confirm the diagnosis by Polymerase Chain Reaction (PCR). Of the 34 dogs, nine (26.47%) had a diagnosis confirmed by PCR, confirming the presence of the parasite in the peripheral circulation of the animal and maintaining the consequent risk of the disease cycle. There was also a lack of knowledge of the owners about the symptoms of human Chagas disease, vector characteristics, general preventive measures of the disease susceptibility of dogs, symptoms, cure and vaccine canine Chagas disease, and the habit of accumulating matter organic outside the home, which acts as a risk factor for the occurrence of the disease in animals and men who share the same environment. However, there was no association between this environmental risk factor or between people's knowledge about the disease and positivity of dogs. About the CHA, it was found that although these show know the susceptibility of humans to the disease, its symptoms, the vector and measures to prevent it, they do not know the etiologic agent, the mechanisms of transmission and prevention of the same.It was also found that there is little inclusion of health education activities related to the Chagas disease in their daily work and conditions offered by the municipality are unsatisfactory. Thus, the research highlights the importance of establishing monitoring programs for Chagas infection in domestic animals and from this, health services can identify areas at risk of transmission, and encourage education work in more emphatic by the CHA health in these areas. As a consequence, the population at risk know more about the disease and ways to prevent it, and thus there will be more successful in the prevention and control the disease
Chagas disease in dogs: analysis of risk factors and health education
Keywords: American trypanosomiasis; Dogs; PCR; Knowledge; Tripanossomíase americana; Cães; PCR; Conhecimento; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE